O ABC de Paulo Freire: presença do ideário freiriano na contemporaneidade das metrópoles brasileiras - Solha, Nelson José dos Santos (2012)
Our research aimed to investigate the presence of the freirianideas in the educational practices developed at the Youngsters and Adults Literacy Movement of ABC (MOVA ABC). We desired to learn how the concepts of dialogicity, knowledge of made experience and vocation to be more, have been appropriated and at what time they were manifested. Methodological procedures included bibliographic review and document analysis. Semi-structured interviews were madewith educators, syndicalist, volunteers and Labor Pastorals members involved in that process, to obtain data, as well as the documents on literacy policies. We also conducted bibliographic studiesaiming a better comprehension of Metropolitan Area where those educational experiences took place. After the analysis and interpretation of results, we can state that there is a strong presence of freirian ideas, as well as the presence of the categories we elected, in the practices of MOVA ABC. Even though there are many challenges present, for example, the risk of discontinuity of the movement at each government at ABC s city hall, they are aware of this aspect and it has not prevented the pursue of the development of even more transforming quality education, by the means of an action and reflection work.